(untitled) (Bangladesh Agronomy Journal, 2017)
The experiment was conducted at the Agronomy research field of Bangladesh Agricultural University, Mymensingh from July to December 2013 to find out the effect of seedling age and storage duration on growth and yield of wet season rice. The experiment comprised of four ages of seedling (25, 30, 35 and 40-d-old) and four storage durations (0, 1, 2 and 3-days) of uprooted seedlings. Rice var. BRRI dhan52 was used as a test variety. The experiment was laid out in a split-plot design with 3 replications placing seedling age in the main plot and storage duration in the sub- plot. The effect of age and storage -duration of seedling, and their interaction were significant on growth parameters (shoot height, root length, number of tillers hill-1, leaf area index and crop growth rate), grain yield and straw yield. The growth parameters and yield exhibited a trend of decrease with the increase in seedling age and storage duration. All the growth parameters and yield showed highest value in the younger seedlings of 25-d-old with 0-day storage duration of uprooted seedlings while the lowest in the older seedlings of 40-d-old with 3-days of storage duration. The var.BRRI dhan52 produced the highest LAI (8.23), CGR (7.33 mg day-1 hill-1) and biomass (26.87 g) at 60, 45 and 60 days after transplanting. Grain yield reduced by 13, 19 and 37% of 30, 35 and 40-d-old seedlings, respectively compared to 25-d-old seedlings. In case of seedling storage, grain yield reduced by 5, 14 and 31% of 1, 2 and 3-d storage, respectively compared to 0-d storage. For optimum growth and yield of wet season rice, 25-d-old seedlings may be stored up to 1-day after uprooting taking into account the possible delay in transporting seedlings to the flood affected area from the nearby districts. Bangladesh Agron. J. 2017, 20(1): 45-56